(untitled) (Global Journal of Human-Social Science, 2023)
This contribution forms part of an extensive effort conducted by the academic literature of constitutional law to immediately reflect the extraordinary and unprecedented constitutional challenges entailed by the virus concerns 3 Although the fact that several contributions have been published during the last months from these issues within a relatively short timeframe we are still at the initial stage of assessing the constitutional implications in their entirety and complexity